Ticks (Acari: Ixodidae) within various phytophysiognomies of a Cerrado reserve in UberlA cent ndia, Minas Gerais, Brazil - Veronez, Viviane Aparecida [UNESP]; Freitas, Beatriz Zanolli; Martins Olegario, Maria Marlene; Carvalho, William Mendes; Tolesano Pascoli, Graziela Virginia; Thorga, Khelma; Garcia, Marcos Valerio [UNESP]; Juan Szabo, Matias Pablo (Springer, 2010)
Cerrado biome, the South American savannah, covers about 2 million km(2) and is very rich in endemic species but threatened by agriculture. In this report free-living tick species are presented, and their seasonal and relative distribution within the various phytophysiognomies in a small Cerrado reserve in Minas Gerais State, Brazil. Overall 2,694 free-living ticks were found during a 2 years sampling period with CO(2) traps and cloth dragging. of these, 73.5% were Amblyomma cajennense and 0.6% Amblyomma dubitatum. All other ticks (25.9%) were retained as Amblyomma spp. Adults of A. cajennense peaked in spring, the nymphs in winter of both years. Amblyomma larval clusters were found in autumn and winter. Adult ticks (46.7%) and nymphs (39.5%) were most often found in woodlands, whereas most larval clusters were found in valley-side marshes (39%). Amblyomma cajennense, Anocentor nitens, Rhipicephalus (Boophilus) microplusand Rhipicephalus sanguineus ticks were found on domestic animals from neighboring properties. Search for Rickettsia in the hemolymph of 497 A. cajennense and one A. dubitatum ticks yielded negative results. Results confirmed earlier reports on the overwhelming prevalence of A. cajennense ticks in the Cerrado biome of Brazil and added information to habitat preferences of this tick species, a major vector in Brazil of the Rocky Mountain spotted fever.
Keywords: Ixodidae; Cerrado; Amblyomma cajennense; Seasonality; Brazil; Phytophysiognomy